Performance analysis of uplink scheduling algorithms in the urban and rural environments in LTE / Shafinaz Ismail, Darmawaty Mohd Ali and Norsuzlia Ya'acob - Ismail, Shafinaz; Mohd Ali, Darmawaty; Ya'acob, Norsuzlia (UiTM Press, 2018)
Long Term Evolution (LTE) is the evolution of an existing 3G mobile network towards a higher capacity, a lower latency and a more efficient core network and radio access. LTE was chosen in order to deliver higher data rate and application demands with trustworthy and reliable connections. This paper makes an attempt to study and compare the performance of two well-known uplink schedulers namely, First Maximum Expansion (FME), and Round Robin (RR). The evaluation is considered for a single cell with three flows, which are the Best Effort, video, and VoIP in an urban and rural environment using the LTE-SIM network simulator. The comparative study is conducted in terms of system throughput, fairness index, delay and packet loss ratio (PLR). The simulation results show that RR algorithm always reaches the lowest PLR among those strategies and RR is the most suitable scheduling algorithms for VoIP and video flows while FME is better for BE flows in both urban and rural environment in LTE networks.